Sorption of imazapic and imazapyr herbicides on chitosan-modified biochars - Yavari, S. (Springer, 2020)
This study aimed to synthesize chitosan-modified biochars with the objective of producing an efficient biosorbents for immobilization of imazapic and imazapyr herbicides in soil. Two biochars were produced separately from oil palm empty fruit bunches and rice husk biomasses and then modified with chitosan in a nitrogen gas environment. The biosorbents characterization showed that biochars modification with chitosan decreased their total surface areas. However, their cation exchange capacities significantly increased. The outcomes alsoÂ showed that soil amendment with chitosan-modified biochars remarkably enhanced its capacity for sorption of imazapic and imazapyr herbicides as compared with pure soil and soil amended with unmodified biochars. Based on the linear distribution coefficients, the capacity of soil for imazapic sorption enhanced by 50 after mixing with unmodified empty fruit bunches biochar, and by 73 after amendment with the chitosan-modified empty fruit bunches biochar. For imazapyr herbicide, soil sorption capacity improved by 8 owing to amendment with unmodified empty fruit bunches biochar, and by approximately 84 after mixing with chitosan-modified empty fruit bunches biochar. Likewise, amendment of soil with unmodified and chitosan-modified rice husk biochars increased its sorption capacity for imazapic herbicide by 25 and 36, respectively, and for imazapyr herbicide by 36 and 67, respectively. Freundlich and Langmuir adsorption isotherms showed similar trends. In conclusion, biochar modification with chitosan would remarkably improve their sorption capacity for imidazolinone herbicides including imazapic and imazapyr herbicides. Â© 2020, Islamic Azad University (IAU).